Vitamin D and mortality - Pilz, Stefan; Grübler, Martin; Gaksch, Martin; Schwetz, Verena; Trummer, Christian; Ó Hartaigh, Bríain; Verheyen, Nicolas; Tomaschitz, Andreas; März, Winfried (Anticancer research, 2016)
In this narrative review, we aim to summarize and discuss the current evidence linking vitamin D and mortality. Low 25-hydroxyvitamin D [25(OH)D] concentrations are associated with an increased risk of mortality. This has been shown in different cohort studies including general populations, as well as various patient cohorts. Some single-study results and meta-analyses indicate that the shape of the relationship between 25(OH)D and mortality follows a U- or a reverse J-shaped curve. Interassay and laboratory differences are, however, a limitation of most previous surveys, and standardization of 25(OH)D measurements is needed for future investigations. Apart from observational data, it has been documented in meta-analyses of randomized controlled trials that vitamin D3 supplementation is associated with a moderate, yet statistically significant, reduction in mortality. This latter finding must be interpreted in light of some limitations such as incomplete follow-up data, but such a reduction of mortality with vitamin D3 supplementation as the finding of meta-analyses of randomized controlled trials strongly argues for the benefits and, importantly, also the safety of vitamin D.